PENERAPAN PROSEDUR CHECK-IN PADA DEPARTEMEN FRONT OFFICE HOTEL GRAND JATRA PEKANBARU - Sundari, Mutia Ayu; ,, Etika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to examine how the check-in procedure is implemented by Guest Service Agents (Receptionists) in the Front Office Department of Grand Jatra Hotel Pekanbaru, as well as to identify the obstacles encountered during its implementation. The background of the research highlights the importance of professional check-in services in creating a positive first impression for guests, especially in five-star hotels that face intense competition in the hospitality industry. The research uses a descriptive qualitative method, with data collection techniques including observation, in-depth interviews, and documentation. The informants consist of the front office manager, supervisor, receptionist, and several hotel guests. The results show that the check-in procedure is generally implemented in accordance with the Standard Operating Procedures (SOP). However, challenges such as limited staff, demanding work schedules, and a lack of training have led to several guest complaints, particularly regarding the hospitality and speed of service. This study concludes that improving service quality and human resource management is essential to achieving optimal guest satisfaction. Keywords: Check-In Procedure, Receptionist, Front Office, Hotel Service, Grand Jatra Hotel Pekanbaru